ANEKA MANFAAT PENGGUNAAN KOMPOS CAIR (LARUTAN DRANCO) BASIL PROSES FERMENTASI ANAEROBIK DENGAN BAHAN BAKU SAMPAH KOTA - R Sudradjat (Jurnal Penelitian Hasil Hutan, 1992)
Dranco  (Dry Anaerobic Conversion) process  is anaerobic  fermentation to produce biogas and paste  residue.  Through pressing,   the  residue  will yield  solid compost (humotex) and liquid compost  (Dranco  liquid). The aim of  this inveatigation is  to know   the  effect   of  the  utilization  of dranco   liquid  when applying it as compost  either  the  effect   on  soil or plant.The  results  showed  that  Dranco  liquid  contained very  low P.  Ca, Mg,  Fe, Mn.  Zn  and  heavy  metals Kj-N,  K and Na   were also  low  but  high enough   when  comparing  with  other nutrients in Dranco  liquid.  The NH4+ was ranked  as high.Addition  of  Dronco  liquid  brought about  an increase  of  E.C  3 - 6 times  depends on  soil  types  ,and liquid  concen- trotion, while soil pH  increased  1.5 -  2 level. The highest growth of maize  was achieved when  soil was mixed with  Dranco  liquid  that  was diluted  2 -  10  times.  Besides,  addition of  Draneo  liquid can maintain  the life of  maize plant  under  water lacking  condition.  Addition  of  Drenco   liquid  increased soil  agregate  stability   2 - 2 0 times  depends  on  soil  types and Dranco   liquid  concentration.  Nitrification process  was  able  to  convert   NH4+  in  the  Dranco liquid   to  N03-  with an  efficicncy  capacity  of  35 %. As a conclusion,  Dranco  liquid is useful to be used as compost liquid  for increasing  soil fertility  as well as promoting plant  growth.